Variation in nutrient-acquisition patterns by mycorrhizal fungi of rare and common orchids explains diversification in a global biodiversity hotspot - Nurfadilah, S.; Swarts, N.; Dixon, Kingsley; Lambers, H.; Merritt, D. (2013)
Background and Aims: Many terrestrial orchids have an obligate requirement for mycorrhizal associations to provide nutritional support from germination to establishment. This study will investigate the ability of orchid mycorrhizal fungi (OMF) to utilize a variety of nutrient sources in the nutrient- impoverished (low organic) soils of the Southwest Australian Floristic Region (SWAFR) in order to effectively compete, survive and sustain the orchid host. Methods: Mycorrhizal fungi representing key OMF genera were isolated from three common and widespread species: Pterostylis recurva, Caladenia flava and Diuris corymbosa, and one rare and restricted species: Drakaea elastica. The accessibility of specific nutrients was assessed by comparing growth including dry biomass of OMF in vitro on basal CN MMN liquid media. Key Results: Each of the OMF accessed and effectively utilized a wide variety of nutrient compounds, including carbon (C) sources, inorganic and organic nitrogen (N) and inorganic and organic phosphorus (P). The nutrient compounds utilized varied between the genera of OMF, most notably sources of N. Conclusions: These results suggest that OMF can differentiate between niches (micro-niche specialization) in a constrained, highly resource-limited environment such as the SWAFR. Phosphorus is the most limited macronutrient in SWAFR soils and the ability to access phytate by OMF indicates a characterizing functional capacity of OMF from the SWAFR. Furthermore, compared with OMF isolated from the rare D. elastica, OMF associating with the common P. recurva produced far greater biomass over a wider variety of nutritional sources. This suggests a broader tolerance for habitat variation providing more opportunities for the common orchid for recruitment and establishment at a site.